A recursive dynamic computable general equilibrium analysis of value-added tax policy options for Nigeria - Alarudeen Aminu (Journal of Economic Structures, 2019)
The study investigates how government can implement an increase in the rate of value-added tax (VAT) to ensure that the final rate of 15% is achieved in a way that satisfies the public (households and business community) and also ensures maximum revenue generation for the government. The nation's VAT rate is presently at 5%. A recursive dynamic CGE model is used to address the study's objective, and the model is solved and simulated for 10 years. It is found that the best policy option is to increase the rate by 2.5% yearly for the next 4 years. The option delivers the best outcomes for real GDP (and its growth), investment, intermediate imports, government expenditure and household consumption when compared to alternative options that require 5% increase (implemented in the first and fourth years) and 10% increment (implemented in the first year). Government revenue (divided into VAT, tax and total revenue) registers the highest percentage changes under 2.5% VAT policy in the medium term (6-10 years).
Keywords: C68; D58; D6; E62; H22; H3; 330; Computable general equilibrium; Value-added tax; Tax policy options; Government revenue; Welfare